Expans\~ao econômica e aumento da formalizaç\~ao das relaç\~oes de trabalho: Uma abordagem através das contrataç\~oes - Carlos Henrique L. Corseuil; Miguel N. Foguel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– We investigate both theoretically and empirically the relationship between economic expansion and the degree of formalization of the Brazilian labor market in the recent period. Based on search models, we present a theoretical framework that attempts to explain the recent increase in the share of formal employment through the dynamics of hiring strategies of firms during the period of expansion of economic activity. The main predictions of this framework are that the share of formal employment rises as the unemployment rate falls and that the wage gap between formal and informal workers increases, at least at the beginning of the economic expansion. In the empirical part, we make use of data from the Pesquisa Mensal de Emprego (PME)/Instituto Brasileiro de Geografia e Estatística (IBGE) to check whether these two predictions are confirmed. To a large extent our results corroborate both predictions.
Keywords: J42; O17; J62; 330; Arbeitsmarkt; Erwerbstätigkeit; Konjunktur; Suchtheorie; Personalbeschaffung; Brasilien